2019
DOI: 10.1002/ppul.24275
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturations and neurodevelopmental outcomes in single ventricle heart disease

Abstract: Objectives To evaluate whether the degree of hypoxemia following stage‐I and stage‐II palliative surgeries predicts neurodevelopmental outcomes at 14 months of age in children with single ventricle congenital heart disease (SVCHD). Design We analyzed longitudinal data from two Pediatric Heart Network (PHN) randomized controlled trials, with a total of 328 subjects. Oxygen saturations, measured via pulse oximetry, at time of discharge from stage‐I and stage‐II surgeries were the primary predictors of interest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“… 46 In a cohort of 328 children with single-ventricle physiology from the Pediatric Heart Network, Wolfe et al found no relationship between peripheral oxygen saturations following state I and stage II palliative surgeries and neurodevelopmental outcomes at 14 months, even when controlling for relevant covariates (any SpO 2 <80% relative risk 2.25 [95% confidence interval (CI) −1.55, 6.06], p = 0.247). 47 …”
Section: Neurodevelopment In Patients With Chdmentioning
confidence: 99%
“… 46 In a cohort of 328 children with single-ventricle physiology from the Pediatric Heart Network, Wolfe et al found no relationship between peripheral oxygen saturations following state I and stage II palliative surgeries and neurodevelopmental outcomes at 14 months, even when controlling for relevant covariates (any SpO 2 <80% relative risk 2.25 [95% confidence interval (CI) −1.55, 6.06], p = 0.247). 47 …”
Section: Neurodevelopment In Patients With Chdmentioning
confidence: 99%
“…Most studies (58%) used a retrospective, cross-sectional, or mixed study design, while the remaining 42% used a prospective and/or longitudinal design. Less than half of the studies (30/78, 38%) included representative samples that did not exclude severely affected children ( 28 31 , 33 35 , 37 45 , 48 52 , 56 , 60 63 , 74 , 79 , 82 , 84 , 85 ). Notably, 50% of the 78 articles excluded children with various syndromes, and 12% excluded children with cognitive disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the impact of gestational age on neurodevelopmental outcomes in adolescents with single ventricle physiology, relative to the full-term group of 100 patients, the 33 early-term patients scored significantly worse on daily-life executive function ratings, were more likely to carry a diagnosis of attention-deficit/hyperactivity disorder and were more likely to have greater psychiatric symptom severity [48]. Further, a cohort of 68 single ventricle patients demonstrated that sleep-disordered breathing correlated with poorer executive function and lower arterial blood oxygen content was associated with poorer executive functioning [49]. Further, atrioventricular valve regurgitation was related to lower parent-rated adaptive function [49].…”
Section: Developmental Outcomes In Single Ventricle Patientsmentioning
confidence: 93%
“…Further, a cohort of 68 single ventricle patients demonstrated that sleep-disordered breathing correlated with poorer executive function and lower arterial blood oxygen content was associated with poorer executive functioning [49]. Further, atrioventricular valve regurgitation was related to lower parent-rated adaptive function [49].…”
Section: Developmental Outcomes In Single Ventricle Patientsmentioning
confidence: 99%